The Relationship of Adolescents' Knowledge of Child Grooming with Sexual Violence Prevention Attitudes at SMAN 2 Gorontalo - Rahmat Anugerah Manto; Siti Rahma; Nirwanto K. Rahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Sexual violence against children and adolescents is a serious problem that continues to increase and requires special attention from various parties, including educational institutions. One form of violence that is often unaware of is child grooming, which is the perpetrator's attempt to build emotional closeness with the victim as the first step towards sexual violence. Adolescents' knowledge of child grooming plays an important role in shaping a preventive attitude towards such actions. This study aims to determine the relationship between adolescents' knowledge about child grooming and attitudes to prevent sexual violence at SMAN 2 Gorontalo. This study is a quantitative research with a Cross-Sectional approach. The population in this study amounted to 1,147 respondents and a sample of 297 respondents using the Cluster Random Sampling technique. This research instrument uses a questionnaire that has been tested for validity and reliability. Bivariate analysis using the Spearman Rho test. The results of the study obtained a P-Value = <0.001 (< ? (0.05) with a correlation value of 0.527, which means that there is a significant and quite strong relationship between adolescents' knowledge of child grooming and sexual violence prevention attitudes at SMAN 2 Gorontalo. This research is expected to be a reference and can be developed for future research, especially in examining other factors that can affect attitudes to prevent sexual violence.